(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article deals with protection against common rodent pests in intensive apple orchards in Khorezm region, the use of agrotechnical, biological and chemical methods harmful to the environment and human health, and the fight against rodent pests in apple orchards. is to study the effectiveness of using new chemical preparations.